Femtosecond Laser Induced Resonant Tunneling in an Individual Quantum Dot Attached to a Nanotip - Duchet, Maxime; Perisanu, Sorin; Purcell, Stephen T.; Constant, Eric; Loriot, Vincent; Yanagisawa, Hirofumi; Kling, Matthias F.; Lepine, Franck; Ayari, Anthony (ACS Photonics, 2021)
Quantized nano-objects offer a myriad of exciting possibilities for manipulating electrons and light that impact photonics, nanoelectronics, and quantum information. In this context, ultrashort laser pulses combined with nanotips and field emission have permitted renewing nano-characterization and control electron dynamics with unprecedented space and time resolution reaching femtosecond and even attosecond regimes. A crucial missing step in these experiments is that no signature of quantized energy levels has yet been observed. We combine in situ nanostructuration of nanotips and ultrashort laser pulse excitation to induce multiphoton excitation and electron emission from a single quantized nano-object attached at the apex of a metal nanotip. Femtosecond induced tunneling through well-defined localized confinement states that are tunable in energy is demonstrated. This paves the way for the development of ultrafast manipulation of electron emission from isolated nano-objects including stereographically fixed individual molecules and high brightness, ultrafast, coherent single electron sources for quantum optics experiments.
CRIS-Team Scopus Importer:2023-04-20
Keywords: field emission; nanotip; quantum dot; resonant tunneling; ultrafast dynamics